The Impact of the Education Program for Stroke (EPSTRO) on Family Caregivers’ Competence in Home-Based Stroke Care - Husni Husni; Asmawati Asmawati; Kelana Kusuma Dharma (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Background: Stroke is now one of the leading causes of adult disability, with negative effects on both individuals and families. Families have a responsibility to offer nursing care (family caregivers), which includes biological, psychological, social, and spiritual aspects of care. The family's ability to care for stroke victims at home is a major factor in determining the family's role as carers in the work environment of the Community Health Center. The initial survey found post-stroke patients with immobilization disorders, lack of good care by the family, and no structured education program for families. The research aimed to determine the impact of education program for stroke (EPSTRO) on caregiver competency, encompassing knowledge, attitudes, and abilities in caring for individuals with stroke. Methods: This study used a quasi-experimental approach with pre-and post-tests. 30 family carers who had experienced a stroke served as the study's sample. Instruments for collecting data on characteristics, knowledge, attitudes, and actions of caregivers were carried out using the modified Sirait questionnaire (2018). The Wilcoxon signed rank test and dependent t-test with p = 0.05 were used to evaluate the data. Results: According to analysis using the Wilcoxon signed rank test statistic, there is a difference in the median knowledge before and after treatment (p=0.0001 0.05), as well as the median skill level (p=0.0001 0.05). There was a difference in the average attitude before and after the treatment, according to the analysis's dependent t-test findings (p=0.0001, 0.05). Conclusions: The education provided by stroke programs significantly enhances caregiver competency.